2015
DOI: 10.4102/jef.v8i2.113
|View full text |Cite
|
Sign up to set email alerts
|

The impact of incentive schemes on employee productivity in the South African workplace

Abstract: The aim of this article is to determine the impact that various incentive schemes have on employee productivity in the South African workplace. A firm-based model is used to estimate the dimensional relationships (different skill levels, gender-mix, firm size, firm-sponsored training incentives) of the incentive scheme-employee productivity link. The main conclusions of the study are, firstly, that finance-based incentive schemes (especially performance-linked bonus schemes) have a greater positive impact on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The article forms part of the ongoing general debate on employee productivity in the South African workplace. Motivation for this particular study emanates largely from the published results of the Van Zyl (2013) paper that deals with the age-skill employee productivity debate and the Van Zyl (2015) paper that deals with incentive-based employee productivity gains. Both these papers conclude that low employee productivity levels are prevalent in the relatively unionised lowerskilled employee segment of the South African workplace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article forms part of the ongoing general debate on employee productivity in the South African workplace. Motivation for this particular study emanates largely from the published results of the Van Zyl (2013) paper that deals with the age-skill employee productivity debate and the Van Zyl (2015) paper that deals with incentive-based employee productivity gains. Both these papers conclude that low employee productivity levels are prevalent in the relatively unionised lowerskilled employee segment of the South African workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Both these papers conclude that low employee productivity levels are prevalent in the relatively unionised lowerskilled employee segment of the South African workplace. Of particular interest for this study are the results of the Van Zyl (2015) paper in which it is concluded that the non-financial incentivebased (such as employee participation platforms, flexible job design and job rotation) productivity gains in the more unionised lower-skilled employee segment are relatively small compared to the higher-skilled segment. Based on the empirical results of both the Van Zyl (2013) and Van Zyl (2015) papers this particular article focusses specifically on the employee productivity impact of the non-financial employee participation dimension of the lower-skilled non-unionised employee segment.…”
Section: Introductionmentioning
confidence: 99%
“…Kompensasi ini biasanya berupa tunjangan-tunjangan dan fasilitas-fasilitas (Zulkarnaen & Herlina, 2018). Berdasarkan hasil dari penelitian terdahulu menunjukan bahwa terdapat pengaruh signifikan positif antara kompensasi dengan produktivitas kerja (Yamoah, 2013;Kelechi et al, 2016;Van Zyl, 2015;Ahiabor, 2013).…”
Section: Pendahuluanunclassified
“…Research thus far has covered various aspects of firm-based employee productivity. These are, (1) remuneration dispersion (Van Zyl 2010), (2) different age-skill categories (Van Zyl 2013a), (3) qualifications and training levels (Van Zyl 2013b), (4) employee diversity (Van Zyl 2014), (5) incentive schemes (Van Zyl 2015), ( 6) non-unionised participation platforms (Van Zyl 2016), ( 7) in-house training (Van Zyl 2017), ( 8) employee migration to smaller firms (Van Zyl 2019) and ( 9) the implementation of new technology (Van Zyl 2020).…”
Section: Introductionmentioning
confidence: 99%